Prescription Profile of Anti-inflamatory Drugs After Excision Biopsy of Oral Soft Tissue Disease in Palembang - Kemas Muhammad Deky Berryl Ananta Putra; Siti Rusdiana Puspa; Nita Parisa (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2022)
Introduction: Oral soft tissue lesion is an abnormal condition of the oral soft tissue. Clinically this lesion can be seen from the changes of colour and size in the surface of the oral soft tissues. There are various types of lesions in the oral cavity, including primary and secondary lesions. The treatment of each lesion is also different, it can be with non-surgical treatment, or surgical treatment. Biopsy is a surgical treatment procedure where tissue is taken for histopathological examination. The purpose of biopsy is to help establish a diagnosis and determine the prognosis of a treatment. After an excisional biopsy, dentists usually give patients anti-inflammatory as a pain control. Anti-inflammatory drugs devide into two groups, steroid and non-steroidal drugs. The most commonly used are non-steroidal groups. The use of anti-inflammatory drugs is seen based on the best therapeutic effects and the fewest side effects. Purpose: The purpose of this study was to examine the prescription profile of anti-inflammatory drugs after excision biopsy of soft tissue disease performed by dentists in Palembang. Method: This research was a descriptive study with survey technique. This research was conducted at the dentist's practice and the hospital's dental clinic in Palembang. Data was collected using a questionnaire form which was filled in by the respondents themselves. The questionnaire consists of several questions that were considered representative to find out how the prescription profile of anti-inflammatory use after excision biopsy of oral soft tissue disease by dentists and or specialist in Palembang. Results: The results of the study showed that the frequency distribution of anti-inflammatory drugs used by dentists in Palembang after excision biopsy was diclofenac (52.5%) and tablet preparations are the main choice (92.5%). Conclusion: The most widely used prescription of anti-inflammatory drugs after excision biopsy of oral soft tissue disease by dentists in Palembang was diclofenac, and tablet preparation of anti-inflammatory drugs was most prescribed by dentist in Palembang.